تأثير استخدام كرتون عربي على ترقية مهارة الاستماع لدى طلاب الصف الثاني في المدرسة المتوسطة بمعهد سبيل المؤمنين تندم هيلير: The effect of Using an Arabic Cartoons to improve Listening Skills of Children in Grade 2 at Tsanawiyah Islamic Boarding School in Tandem Hilir - Candra, Jeki; Ahmad Zaky; Muhammad Sapi’i Harahap (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Abstract: Arabic comprises four abilities and four components, namely speaking, reading, writing, and listening. The aim of this study is to knowledge the effect of using Arabic cartoons to improve listening skills of children in Grade 2 at Tsanawiyah Islamic Boarding School in Tandem Hilir, North Sumatra. The researcher use quantitative approach with experiment method. This study compares the students' listening abilities before and after the application of Arabic cartoons. According to the study's findings, pupils overall scored 1853 on the pretest. The average score is 61.8; pupils who receive the predicate pass 9 individuals while those who do not pass 21 individuals. The posttest exam had a total score of 2663, but the average was 88.76, with 30 students receiving the passing predicate and none receiving the failing predicate. The influence of Arabic cartoons on listening skills is another factor. The value of 2,04<17,197>2,75 indicates that to is greater than tt. Ha is therefore accepted but Ho is refused. Keywords: Education, Arabic Cartoons, Listening Ability مستخلص البحث: اللغة العربية لها أربع مهارات وأربع عناصر هي الاستماع والكلام والقراءة والكتابة، ويهدف هذا لمعرفة تأثير استخدام "كرتون عربي" على ترقية مهارة الاستماع لدى طلاب الصف الثاني في المدرسة المتوسطة بمعهد سبيل المؤمنين تندم هيلير سومطرة الشمالية. استخدم الباحث المنهج الكمي بطريقة التجريبية. ونتيجة البحث تدل على أن استعمال "كرتون عربي" هي: المجموعة ١853، والمعدل هو ٦1،٨، ناجح 9 طلاب، غیر ناجح 21 طالبا، وقدرة الطلاب على مهارة الاستماع بعد استعمال "كرتون عربي" هي: المجموعة 2663، والمعدل هو 88,76، ناجح 30 طالبا، غیر ناجح لا يوجد. ويوجد تأثير"كرتون عربي" على مهارة الاستماع لدى طلاب الصف الثاني. وأظهرت النتيجة to أكثر من tt وهي 2,04< 17،197>٢،٧5. فالفرض العدمية مردودة والفرض التبادلية مقبولة. كلمة المرور: التربية، كرتون عربي، مهارة الاستماع